Valproic Acid-Associated Liver Failure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the University of Maryland School of Medicine, Baltimore, and other centers analyzed the records of 17 children undergoing liver transplantation (LT) for valproic acid-associated liver failure (VPA-ALF) and 98 with ALF caused by other drugs (non-VPA-drug-induced acute liver failure [DIALF].